Molla Sadra’s critiques on the Ibn Sinas’ account of proof from contingency and necessity - Aflatun Sadeghi (حکمت صدرایی, 2017)
One of the well-known arguments for the existence of God is “proof from contingency and necessity”. It was Avicenna who first, in his works, formulated this argument. This argument has been criticized by Gazzali, Averroes and Molla Sadra, in the world of Islam and by Hume, Kant, Russell and others in the west. Mulla Sadra has criticized Ibn Sinas’account of proof from contingency and necessity directly and indirectly. These critiques that has come into his works are the incorrectness of quality of this argument, the use of vicious circle and infinite regress, the use of non-concrete being instead of real being, and the fallacy of composition. Considering these critiques shows validity or inefficiency of them.This article seeks to make clear the correctness or incorrectness of these critiques in a descriptive, analytic and critical way.